2018
DOI: 10.1016/j.bbabio.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the F-domain in [FeFe] hydrogenase

Abstract: The role of accessory Fe-S clusters of the F-domain in the catalytic activity of M3-type [FeFe] hydrogenase and the contribution of each of the two Fe-S surface clusters in the intermolecular electron transfer from ferredoxin are both poorly understood. We designed, constructed, produced and spectroscopically, electrochemically and biochemically characterized three mutants of Clostridium acetobutylicum CaHydA hydrogenase with modified Fe-S clusters: two site-directed mutants, HydA_C100A and HydA_C48A missing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 54 publications
2
52
0
Order By: Relevance
“…It has repeatedly been shown that [FeFe]-hydrogenases can operate at minimal overpotentials, albeit specic enzymes generally display a bias for either H + reduction or H 2 oxidation. [31][32][33][34] Indeed, even in the relatively narrow selection of enzymes studied to-date signicant differences in catalytic rates, stability of different H-cluster states and reactivity towards inhibitors (e.g., CO and O 2 ) have been observed. 22,31,[35][36][37][38][39] On a fundamental level, further insight into subclass-specic reactivities is critical for our understanding of hydrogen metabolism, and elucidating the interplay between the H-cluster and the protein.…”
Section: Introductionmentioning
confidence: 99%
“…It has repeatedly been shown that [FeFe]-hydrogenases can operate at minimal overpotentials, albeit specic enzymes generally display a bias for either H + reduction or H 2 oxidation. [31][32][33][34] Indeed, even in the relatively narrow selection of enzymes studied to-date signicant differences in catalytic rates, stability of different H-cluster states and reactivity towards inhibitors (e.g., CO and O 2 ) have been observed. 22,31,[35][36][37][38][39] On a fundamental level, further insight into subclass-specic reactivities is critical for our understanding of hydrogen metabolism, and elucidating the interplay between the H-cluster and the protein.…”
Section: Introductionmentioning
confidence: 99%
“…If H/D exchange measurements using a MIMS allow determining the catalytic constant of H 2 ase, it can also be used to determine the resistance of gas diffusion between the active H 2 ase site and the reaction medium in vitro ( Leroux et al., 2008 ). In vitro H/D exchange measurements have been used to study enzymatic properties of native H 2 ase ( Abou Hamdan et al., 2012 ; Gauquelin et al., 2018 ), including O 2 -tolerant H 2 ases ( Liebgott et al., 2011 ), as well as H 2 ases modified by site-directed mutagenesis in order to limit O 2 diffusion to the active site ( Cano et al., 2014 ). H 2 photoproduction by microorganisms has recently regained huge interest for biofuel production due to recent improvements in strains and experimental protocols ( Tóth and Yacoby, 2019 ).…”
Section: Mims Usage In Algal Researchmentioning
confidence: 99%
“…This has been elucidated in the case of the two closely related M3-type enzymes from CpI and CaI as well as the sub-class M2 enzymes from Megasphaera elsdenii (MeHydA) and DdH. [31][32][33][34] In the latter case, redox titrations combined with FTIR and EPR spectroscopy revealed that the redox equilibrium of the diiron site and its pKa is influenced by the oxidation state of the F-clusters. 33 Parallel studies of CaI and MeHydA have shown that the F-clusters affects the catalytic bias of the enzyme.…”
Section: The Influence Of F-clusters and Protein Environmentmentioning
confidence: 99%
“…In both cases, removal of the F-domain resulted in enzymes favoring H2 release following a significant drop in H2 oxidation rates. 31,32 In addition to the F-clusters the activity of [FeFe]-hydrogenase is influenced by the mass transfer of gases (e.g., H2, O2, or CO) and protons (H + ). Molecular dynamics simulations proposed a number of putative gas channels 35 , and site-directed mutagenesis could slow down O2 inactivation in individual studies.…”
Section: The Influence Of F-clusters and Protein Environmentmentioning
confidence: 99%